(untitled) (Costos y Gestión, 2021)
In the context of globalization, privatization and liberalization, major changes occurred in the educational environment, thus redefining the metrics of excellence for Higher Education. Fierce competition has pushed universities to gradually grant more importance to marketization of education which lead to the repositioning of Higher Education as a global commodity. This caused a paradigm shift, where main drivers of the lucrative business sphere were adopted by universities. The educational industry is since witnessing many reforms where the center of gravity shifted from quality to quantity, therefore transforming the elite model into a mass education system. The commercialization of education contributed in watering down the academic rigor causing a conflict between administrators and academics. Such strategic misalignment impacted the quality assurance’s purpose of yielding a favorable academic environment. This paper is concerned with improving the students’ learning and quality of services in the private higher education sector. Socio-Economic Approach to Management is pursued to help universities better balance between their external and internal environments. This intervention research focuses on enhancing the management and quality of services to achieve higher sustainability and performance by transforming hidden costs into added-value. The SEAM research methodology goes through the steps that compose the HORIVERT process which is composed of 2 main actions, horizontal and vertical. As a result, cohesive findings are created where a full range of qualitative, quantitative and financial information are covered whereby social, economic and financial organizational objectives become integrated with. Based on the intervention results, we conclude that the quality of services teaching and curriculum quality, as well as academic and career counseling services, constitute important determinants of perceived service quality and the influence of the latter construct over student satisfaction.